The Future of Saving : The Role of Pension System Design in an Aging World - Amaglobeli, David (Staff Discussion Notes; Staff Discussion Notes, 2019)
This SDN explores how demographic changes have affected and will affect public and private sector savings, highlighting the interaction between pension systems, labor markets, and demographic variables.